The Effect of Rice Husk Biochar and Cow Manure on Some Soil Characteristics, N and P Uptake and Plant Growth of Soybean in Alfisol - Slamet Supriyadi; Bakti Wisnu Widjajani; Eko Murniyanto (UNIVERSITY OF LAMPUNG, 2022)
The effect of biochar on dryland in Madura has not been fully assessed. The objective of this study was to investigate the effect of biochar and animal manure on some soil characteristics, namely water content at field capacity, CEC, N total, available P, and N and P absorption, and plant growth of soybean in Alfisol. The research was arranged on a Randomized Completely Block Design (RCBD) with four replications. Rice husk biochar was mixed with cow manure and applied at the range of 2.5 - 10 Mg ha-1. The result showed that biochar (2.5 Mg ha-1) and cow manure (7.5 Mg ha-1) improved soil characteristics, plant growth, and soybean yield by 22%. Cow manure in this study would function as a source of nutrients while rice husk biochar acted as storage of nutrients that were then released slowly to soil solution for plant uptake. It was concluded that the mixture of 2.5 Mg rice husk biochar ha-1 and 7.5 Mg cow manure ha-1 could be the best combination of soil amendments to apply in an Alfisol in Madura.